Pengaruh Insentif Terhadap Disiplin Kerja Pegawai Negeri Sipil di PPPPTK TK dan PLB Bandung - Dhineu Herawati Sejati; Aan Komariah; Abu Bakar (Jurnal Tata Kelola Pendidikan, 2019)
This study entitled "The Effect of Incentives to Work Discipline of Civil Servantsin PPPPTK TK and PLB Bandung". This research was carried in education andtraining institutions, technical and operational units Ministry of Education andCulture, employees with civil servant status are involved in the sampling of thisstudy. In general, this study aims to determine how the incentive effect thediscipline of employees working in PPPPTK TK and PLB Bandung. The methodused is descriptive method with quantitative approach, where the technique usedin data collection questionnaire that is enclosed with the number of 75respondents research. Data analysis and processing using the application's helpMicrosoft Excel 2010 and SPSS version 21.0 for Windows. The result of theanalyze of Means Weight Score (WMS), indicates that incentives are in the highcategory, with a score of 3,95 and discipline acquisition included in the categoryof work is very high with the acquisition of a score of 4,29. The results of the data analysis of the correlation coefficient between the incentive to work discipline shows the correlation value is equal to 0,475%, with determination coefficient of 22,5%, meaning that the incentive effect on work discipline civil servants of 22,5%, and the remaining 77,5% is influenced by other factors. The level of significance obtained 0,4607 ˃ 1,666 it means that there is a positive and significant effect between employee incentives with discipline in PPPPTK TK and PLB Bandung.